Uniform Cu/chitosan beads as a green and reusable catalyst for facile synthesis of iminesviaoxidative coupling reaction - Threeraphat Chutimasakul (2020)
© The Royal Society of Chemistry 2020. A nonprecious metal and biopolymer-based catalyst, Cu/chitosan beads, has been successfully prepared by using a software-controlled flow system. Uniform, spherical Cu/chitosan beads can be obtained with diameters in millimeter-scale and narrow size distribution (0.78 ± 0.04 mm). The size and morphology of the Cu/chitosan beads are reproducible due to high precision of the flow rate. In addition, the application of the Cu/chitosan beads as a green and reusable catalyst has been demonstrated using a convenient and efficient protocol for the direct synthesis of iminesviathe oxidative self- and cross-coupling of amines (24 examples) with moderate to excellent yields. Importantly, the beads are stable and could be reused more than ten times without loss of the catalytic performance. Furthermore, because of the bead morphology, the Cu/chitosan catalyst has greatly simplified recycling and workup procedures.